Anxiety over EFL speaking and writing: A view from language classrooms - Gkonou, Christina (Zakład Filologii Angielskiej: Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2011)
The assumption that foreign language learners experience a high level of anxiety mainly when faced with speaking activities implies that research should focus on those learners prone to anxiety over that skill. Despite not being widely investigated, foreign language writing anxiety also seems to be a concern for a large number of students. Drawing on questionnaire findings, the study reported in this article examined the nature of, and the connection between the English language classroom speaking and writing anxiety of 128 Greek EFL learners in private language school settings. Speaking anxiety was operationalised by Horwitz, Horwitz, and Cope's (1986) Foreign Language Classroom Anxiety Scale, and writng anxiety was measured by Gungle and Taylor's (1989) ESL version of the Daly and Miller's 1975) Writing Apprehension Test. Interconstruct and intraconstruct associations between the two instruments were examined through principal components analysis with varimax rotation and correlations check. A significant and high correlation was found between classroom anxiety and speaking anxiety, thus indicating that the English language classroom context is a source of speaking anxiety. Writing anxiety was found to load primarily on items relating to attitudes towards writing in English followed by self-derogation for the process and fear of negative evaluation by the teachers and/or by fellow students. On the basis of the findings, suggestions are made concerning the reassessment of the influence that writing anxiety exerts on classroom performance and the adoption of teaching techniques that promote topic-centred process writing.
Keywords: English language anxiety; Teaching writing; Sociolinguistics of language learning